AB0537 Rhupus: Myth or an Overlooked Fact. an Indian Perspective. (10th June 2014) - Kulkarni, N.; Nahar, N.; Saluja, M.; Venugopalan, A.; Chopra, A.
Abstract : Background: Rhupus; is it an overlap or a distinct entity? First Described in 1960 1, it has received scant attention. There are no diagnostic biomarkers. Objectives: To study the clinical phenotype of RHUPUS Methods: Subjects of RHUPUS were identified retrospectively from database maintained at Centre For Rheumatic Diseases, Pune maintained since 1996 and currently with records of over 35000 patients. The diagnosis was clinical and made by Rheumatologist. Clinical and investigations data, with focus on serology, was extracted pertaining to initial examination and follow up. Study Period 2000-2013. Auto antibodies reported were RF (Nephlometry, cut off 40IU/ml, Anti CCP (Second generation ELISA, cut off 5RU/ml), Anti dsDNA (ELISA, cut off 24IU/ml) and screening of ENA (ELISA, Western Blot) Results: 114 patients with RHUPUS were identified. 57% satisfied 1987 ACR criteria for RA and 44% satisfied 1999 ACR criteria for SLE while 33% satisfied both. The onset was RA like in 50% patients. 56% had symmetrical small and large joint arthritis; 21% were erosive (XRay hands), 5% had subcutaneous nodules. 17% patients presented first as SLE with 7% having renal involvement, 26% neurological, 10% with discoid rash, 2% having serositis, 5% with cytopenias (none AIHA) and 7% had Raynaud's (with digital gangrene). 67% patients were seropositive for Rheumatoid Factor, 42% for ACCP, 58% for ANA and 47% for Anti dsDNA. 50% patients with Predominant RA had serological ANA positivity while 30% with predominant SLE phenotype were detected to have ACCP. During follow up lesser systemic complications were recorded. Overall it appeared to have a better prognosis compared to aggressive RA or SLE. Articular deformities were usually mild. Conclusions: This is probably the largest RHUPUS series reported. The phenotype is heterogenous with several overlap features (RA & SLE) and merits detail immunogenetic exploration to endorse its distinct phenotype if any. It also suggests a relook at the new Classification Criteria's for RA and SLE. References: Toone et al. The American Journal Of Medical Sciences, 1960 Acknowledgements: Arthritis Research & Care Foundation – Center for Rheumatic Diseases. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2891